THE EFFECT OF INTERNSHIP AND EMPLOYER BRANDING ON CAREER INTENTION OF HOSPITALITY DEPARTMENT STUDENTS AT BALI TOURISM POLYTECHNIC - Suartana Putra, I Made; Ni Luh Ketut Sri Sulistyawati; Ni Made Suastini (JURNAL KEPARIWISATAAN, 2025)
The hospitality industry demands graduates who not only master theoretical knowledge but also possess practical readiness and hold a positive perception of employers as an attraction in their career choice. This study aims to examine the effect of internship experience (X?) and employer branding (X?) on career intention (Y) among Hospitality students at Bali Tourism Polytechnic. A quantitative approach with a survey design was employed, involving a sample of 81 final-year students selected from a population of 484 through purposive sampling and stratified random sampling. Primary data were collected using a structured questionnaire and analyzed via multiple linear regression. The results indicate that internship experience has a significant effect on career intention (p = 0.000 < 0.05), whereas employer branding does not exert a significant effect on career intention (p = 0.145 > 0.05). Simultaneously, both variables exert a significant influence on career intention (F-calculated = 184.30 > F-table = 3.11; p = 0.000 < 0.05). Moreover, the variables of internship experience and employer branding together account for 82.1% of the variance in students’ career intention, demonstrating that the relationship between these independent variables and career intention is very strong.